Digitalisasi Layanan Publik, Transparansi Biaya, Akuntabilitas terhadap Kepuasan Pengguna Website Terpadu - Hurian Kamela (CV. Ulil Albab Corp, 2026)
The purpose of this study is to examine the effect of public service digitalization, cost transparency, and accountability on the satisfaction of integrated website users. This study focuses on the implementation of digital public services through integrated government websites, the openness of service cost information, and the accountability of public services provided to the community. This study employed a quantitative approach with a descriptive and causal research design. Data were collected through questionnaires distributed to users of integrated public service websites who had experience accessing digital government services. In general, the results of the study indicate that digitalization of public services, cost transparency, and accountability have a positive influence on user satisfaction. Public service digitalization improves convenience, accessibility, and efficiency in obtaining services, while cost transparency increases public trust through clear and accessible information regarding service fees. In addition, accountability contributes to improving the quality and reliability of digital public services. The findings also show that users tend to feel more satisfied when the website provides accurate information, transparent procedures, and responsive services. Therefore, this study recommends that government institutions continuously improve the quality of digital public services, strengthen transparency in service costs, and enhance accountability to increase public satisfaction with integrated websites.